Prevalence of self-medication practices among urban slum dwellers in Hyderabad, India - Katkuri, Sushma; Chauhan, Pooja; Shridevi, Kotina; Kokiwar, Prashant; Gaiki, Varun (International Journal Of Community Medicine And Public Health, 2016)
Background: In a number of developing countries many drugs are dispensed over the counter without medical supervision. In this case, self-medication provides a lower cost-alternative for people who cannot afford the cost of clinical service. Objectives of the study was to assess the prevalence of self-medication among urban slum dwellers and to find out factors influencing self-medication. Methods: A community based cross-sectional was done in the field practice area of Department of Community medicine. All the residents of selected slum who >18 years of age were selected. A total of 200 participants were randomly selected. Results: The prevalence of self-medication was very high (73%). Majority of the study participants preferred allopathy medicine (84%). Pharmacist was the main source of information for practicing self-medication (67%). Conclusions: Health education sessions should be conducted to create awareness about side effects of self-medication. Strict laws should also be formulated by the concerned authorities that without prescription of doctors no medicine should to given to anybody at the pharmacy.